Symposium 11: Theory and Design of Distributed Networked Learning Communities - McConnell, David; Lally, Vic; Banks, Sheena (Proceedings of the International Conference on Networked Learning, 2004)
The current interest in distributed networked learning communities may be explained, in part, by our need to feel we belong to a group of like-minded people who share out values and beliefs. Distributed networked learning communities focus on developing a culture of learning where members support each other and where no one individual (teacher or student) is responsible for knowing everything. Lifelong learning practitioners (and those involved in continuing professional development) have consistently had an interest in designing for learning communities. The move to Web-based learning environments is now exercising their minds around the question of theoretical designs for networked learning environments that support those values and beliefs they hold to be so important in their practice. Through an in-depth analysis of the theory underpinning the design of an existing distributed networked learning Masters degree course, this paper shows how practitioners involved in lifelong learning courses delivered entirely via the Web can integrate features of computer supported collaborative learning theory into the design to support the educational value of community.